OLD-BOHEMIAN DEATH - Vseticka, Frantisek (Bohemica Olomucensia, 2021)
The Old Bohemian poem Death belongs to the sphere of works with the theme of memento mori, which was already expressed by its theorem-theme. The poem has a two-part strof and includes a distinct introduction and finale. The essence of the poem is created by the passage of the world and the passage of the soul. The entire composition is built on an octavic principle.
Keywords: theorem-theme; strofa; introduction; final; passage of the world; passage of the soul; octavic principle